PENGARUH MOTIVASI GURU AKIDAH AKHLAK TERHADAP PERILAKU RELIGIUS SISWA KELAS VII DI MADRASAH TSANAWIYAH MUHAMMADIYAH WARU BAKI SUKOHARJO - Wahidah, Rizqi Nur; Anshori, Muhammad Isa (Jurnal Manajemen Pendidikan, 2025)
This study aims to examine the influence of Islamic creed and ethics teachers’ motivation on the religious behavior of seventh-grade students at MTs Muhammadiyah Waru Baki Sukoharjo. Teachers play a key role as motivators in shaping students' religious character, yet few quantitative studies have specifically assessed the relationship between teacher motivation and students’ religious conduct at the junior Islamic secondary level. This research employed a correlational quantitative approach with a sample of 63 seventh-grade students. Data were collected through questionnaires for the teacher motivation variable and documentation of students’ spiritual and social behavior scores for the religious behavior variable. The data were analyzed using Pearson Product Moment correlation test. The results indicate that teacher motivation is generally in the moderate category (67%), as is students' religious behavior (62%). The correlation coefficient was found to be 0.775 with a significance level of 0.000, suggesting a strong and significant relationship between teacher motivation and students’ religious behavior. The coefficient of determination was 60.06%, indicating that teacher motivation significantly contributes to students' religious character formation. The implication of this research highlights the essential role of teachers as motivators, role models, and spiritual guides in Islamic character education within the madrasah environment.